2001
DOI: 10.1016/s0370-2693(01)01228-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of ω mesons in proton–proton collisions

Abstract: The cross section for the production of ω mesons in proton-proton collisions has been measured in a previously unexplored region of incident energies. Cross sections of σ = (7.5 ± 1.9) µb and σ = (30.8 ± 3.4) µb (with 20% systematic uncertainties) were extracted at ǫ = 92 MeV and 173 MeV excess energy above the ω threshold, respectively. The angular distribution of the ω at ǫ = 173 MeV is strongly anisotropic,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…The negative value of D N N found was taken as evidence for the dominance of kaon compared to pion exchange [198], but it is important to stress that the possibility of ρ exchange was not considered in this discussion. In contrast, the early COSY-TOF differential cross section results came down in favour of non-strange meson exchange by showing that the pp → K + pΛ data have evidence for the excitation of N * isobars in the final K + Λ channel [216,217]. This approach has far less model dependence than the D N N studies.…”
Section: Differential Distributionsmentioning
confidence: 94%
See 4 more Smart Citations
“…The negative value of D N N found was taken as evidence for the dominance of kaon compared to pion exchange [198], but it is important to stress that the possibility of ρ exchange was not considered in this discussion. In contrast, the early COSY-TOF differential cross section results came down in favour of non-strange meson exchange by showing that the pp → K + pΛ data have evidence for the excitation of N * isobars in the final K + Λ channel [216,217]. This approach has far less model dependence than the D N N studies.…”
Section: Differential Distributionsmentioning
confidence: 94%
“…The COSY-TOF collaboration found that the S 11 (1650) plays a prominent role near threshold and there are certainly similarities with the pp → ppη reaction, which is dominated by the analogous S 11 (1535) near threshold. Away from the threshold region the group also found evidence from the Dalitz plots for the importance of the P 11 (1710) and/or the P 13 (1710) isobars in Λ production [216,217].…”
Section: Differential Distributionsmentioning
confidence: 94%
See 3 more Smart Citations